2009
DOI: 10.1111/j.1745-4549.2008.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Wireless Versus Standard Thermocouples for Data Gathering and Analyses in Rotary Cookers

Abstract: The performance of a wireless temperature sensor was compared with that of a conventional thermocouple for gathering heat penetration data. A central composite rotatable design experimental design with three different processing conditions (glycerin concentration [70–100%], retort temperature [111.6–128.4C] and retort speed [4–24 rpm]) were employed using 307 × 409 cans containing the particulate fluid to compare the performance of the two devices. Experiments were performed in a fixed axial mode of rotation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For data gathering under such situations, researchers have used self-contained wireless sensors which gather data continuously and transmit signals to a computer. Dwivedi and Ramaswamy (2010b) showed that there were no statistical differences between the performance of wireless systems compared to conventional systems and in fact, the wireless sensors were reported to be relatively more stable for rotary autoclaves especially for free axially rotating cans. By adopting wireless technology, 20-80% of the wiring costs in industrial application can be eliminated and also gives a chance of real time tracking of the free movement of particles (Wang et al, 2006).…”
Section: Data Collection Via Wireless Sensorsmentioning
confidence: 95%
See 3 more Smart Citations
“…For data gathering under such situations, researchers have used self-contained wireless sensors which gather data continuously and transmit signals to a computer. Dwivedi and Ramaswamy (2010b) showed that there were no statistical differences between the performance of wireless systems compared to conventional systems and in fact, the wireless sensors were reported to be relatively more stable for rotary autoclaves especially for free axially rotating cans. By adopting wireless technology, 20-80% of the wiring costs in industrial application can be eliminated and also gives a chance of real time tracking of the free movement of particles (Wang et al, 2006).…”
Section: Data Collection Via Wireless Sensorsmentioning
confidence: 95%
“…Various techniques have been developed for monitoring particle temperatures during agitation. Depending on the purpose of collection of heat penetration data, these techniques may range from the use of normal thermocouples (Deniston et al, 1987;Meng, 2006;Sablani, 1996) to the use of other technologies like wireless sensors (Awuah et al, 2007b;Dwivedi and Ramaswamy, 2010b;Lesley, 1987;Wang et al, 2006), time-temperature indicators like liquid crystals (Balasubramaniam and Sastry, 1995;Stoforos and Merson, 1991;Zitoun andSastry, 1994) and, chemical (Van Loey et al, 1995;Hendrickx et al, 1995;Weng et al, 1992) and biochemical indicators (Pflug et al, 1980a(Pflug et al, , 1980bSilva et al, 1994). …”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 2 more Smart Citations